SARS-CoV-2 Omicron Variants Reduce Antibody Neutralization and Acquire Usage of Mouse ACE2 - Wang, Ruoke; Zhang, Qi; Zhang, Rui; Aw, Zhen Qin; Chen, Peng; Wong, Yi Hao; Hong, Junxian; Ju, Bin; Shi, Xuanling; Ding, Qiang; Zhang, Zheng; Chu, Justin Jang Hann; et al. (Frontiers in Immunology, 2022)
Striking number of mutations found in the spike protein of recently emerged SARS-CoV-2 Omicron has raised serious concerns regarding the escape from current antibody therapies and vaccine protection. Here, we conducted comprehensive analysis on the extent of Omicron BA.1, BA.1.1, and BA.2 to escape neutralization from the therapeutic antibodies approved by the regulatory authorities and convalescent plasma from SARS-CoV-2 patients infected during initial wave of pandemic in early 2020. Among the variants tested, Omicron BA.1 and BA.1.1 were the most resistant in both magnitude and breadth against antibodies and convalescent plasma, followed by Beta, BA.2, Gamma, Delta and Alpha. While the majority of therapeutic antibodies markedly reduced or completely lost binding and neutralization to Omicron variants, BRII combo (BRII-196 + BRII-198), S309, and AZ combo (COV2-2196 + COV2-2130) maintained neutralization due to either conserved epitope or combinational effect between the two designated antibodies. A single intraperitoneal injection of BRII combo as a prophylactic treatment protected animals from Omicron infection. Treated animals manifested normal body weight, survived infection up to 14 days, undetectable levels of infectious viruses in the lungs, and reduced lung pathology compared to the controls. Analyzing ACE2 from diverse host species showed that Omicron variants acquired ability to use mouse ACE2 for entry. These results demonstrate major antigenic shifts and potentially broadening the host range of Omicron variants, posing serious challenges to current antibody therapies and vaccine protection as well as increasing danger of spillover into the wildlife.